Lipid-Based Nanoparticles in Delivering Bioactive Compounds for Improving Therapeutic Efficacy - Patel, Priya; Garala, Kevinkumar; Singh, Sudarshan; Prajapati, Bhupendra G.; Chittasupho, Chuda (Pharmaceuticals (Basel, Switzerland), 2024)
In recent years, due to their distinctive and adaptable therapeutic effects, many natural bioactive compounds have been commonly used to treat diseases. Their limited solubility, low bioavailability, inadequate gastrointestinal tract stability, high metabolic rate, and shorter duration of action limited their pharmaceutical applications. However, those can be improved using nanotechnology to create various drug delivery systems, including lipid-based nanoparticles, to adjust the compounds’ physicochemical properties and pharmacokinetic profile. Because of the enormous technical advancements made in the fundamental sciences and the physical and chemical manipulation of individual atoms and molecules, the subject of nanotechnology has experienced revolutionary growth. By fabricating certain functionalized particles, nanotechnology opens an innovative horizon in research and development for overcoming restrictions, including traditional medication administration systems. Nanotechnology-driven bioactive compounds are certain to have a high impact and clinical value for current and future uses. Lipid-based nanotechnologies were shown to deliver a range of naturally occurring bioactive compounds with decent entrapment potential and stability, a successfully controlled release, increased bioavailability, and intriguing therapeutic activity. This review outlines bioactive compounds such as paclitaxel, curcumin, rhodomyrtone, quercetin, kaempferol, resveratrol, epigallocatechin-3-gallate, silymarin, and oridonin, fortified within either a natural or synthetic lipid-based drug delivery system based on nanotechnology and their evaluation and clinical considerations.